PENGARUH CREDIT RATING DAN RATING OUTLOOK TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN YANG TERDAFTAR DI PEMERINGKAT EFEK INDONESIA - Sadya Datu Amudra Rochaddi; Surya Raharja (Diponegoro Journal of Accounting, 2023)
This study aims to analyze the effect of credit rating and outlook rating on going concern audit opinions. The dependent variable in this study is the going concern audit opinion, while the independent variables in this study are the credit rating and rating outlook. This research uses quantitative methods. The population in this study is made up of non financial sector companies registered with the Indonesian Securities Rating Agency (PEFINDO). The sample selection technique uses purposive sampling. The statistical method used to test the hypothesis in this study is logistic regression analysis. The results of this study indicate that credit ratings have no significant positive effect on going-concern audit opinions. Rating Outlook has a significant positive effect on going concern audit opinion. The implications of this research are expected to be taken into consideration by companies in their efforts to pay off debts because when a company is unable to pay off its debt obligations, the company's credit rating and outlook rating have the potential to decrease, so the auditor has a high probability of giving a going concern audit opinion to a company.